Tube and Sheet Metal Forming Processes and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
At present, the manufacturing industry is focused on the production of lighter weight components with better mechanical properties and always fulfilling all the environmental requirements. These challenges have caused a need for developing manufacturing processes in general, including obviously those devoted in particular to the development of thin-walled metallic shapes, as is the case with tubular and sheet metal parts and devices.This Special Issue is thus devoted to research in the fields of sheet metal forming and tube forming, and their applications, including both experimental and numerical approaches and using a variety of scientific and technological tools, such as forming limit diagrams (FLDs), analysis on formability and failure, strain analysis based on circle grids or digital image correlation (DIC), and finite element analysis (FEA), among others.In this context, we are pleased to present this Special Issue dealing with recent studies in the field of tube and sheet metal forming processes and their main applications within different high-tech industries, such as the aerospace, automotive, or medical sectors, among others.